Implementasi Ketentuan Kuota 30% Keterwakilan Perempuan Di DPRD Kota Salatiga - Raqim, Ukhti; Lestari, Puji; Handoyo, Eko (Unnes Political Science Journal, 2017)
The reality of politics showed the low representation of women in Regional House of Representatives (DPRD) and was under proportion, it indicated that the women representation in political life was ignored. The demand of gender equality was also increasing, so that the goverment issued Acts Number  8 of 2012 and KPU Regulations which some of their articles regulated about the 30% women representation. This case was also occured in Salatiga City. In the 2004 legislative election, there were only 5 women who got the seats. In 2009 there were 7 women and in 2014 there were still only 7 women. The problems that were investigated in this study were 1) How the implementation of 30% quota of women regulation fulfillment in DPRD of Salatiga City was, 2) What obstacles in fulfilling the 30% quota of women representation in Salatiga City were. This study used qualitative methods. The methods of collecting data in this study were observation, interview, and documentation. The methods of validating data used sources triangulation. Data analysis used Miles and Huberman qualitative data analysis which consists of 1) data collection, 2) data reduction, 3) data presentation, 4) conclusion.  The results of the study showed that: 1) 30% quota regulation had been implemented, however it did not succeed. Although the 30% quota was not fulfilled, the members of Salatiga City DPRD increased from 2004-2009. The 2004-2009 period reached 5 women, in 2009-2014 there were 7 women, and in 2014-2019 were also 7 women, and it only reached 28%. 2) the problems were the lack of effort of political parties in performing, implementing, and fighting for activities and interests of women that made those activities were not working, and the powerful social construction in citizens, especially in women themselves. Based on these results, the researcher suggested that 1) The demand to increase the women representation must be balanced with efforts to assure that women who will be peopleâs representatives are really qualified in leading people, understanding womenâs interests and willing to figh for them. 2) To the stakeholders or policies implementer, they must give more efforts in promoting gender education or political education through the empowerment of women to change peopleâs perceptions or mindsets, especially for women who think they cannot compete with men.